Improving Grade VIII Students’ Vocabulary Mastery through Flashcards at SMP Negeri 7 Palu - Tika Tika; Mawardin M Said; Andi Patmasari (Journal of General Education and Humanities, 2026)
Students’ limited vocabulary mastery remains a challenge in learning English at the junior high school level. This study aims to examine the effectiveness of using flashcards in improving the vocabulary mastery of Grade VIII students at SMP Negeri 7 Palu. This research applied a quasi-experimental design with a non-equivalent control group design. The sample consisted of 58 students, including 29 students in the experimental class (VIII F) and 29 students in the control class (VIII E). Data were collected through pre-test and post-test to measure students’ vocabulary mastery before and after the treatment. The results of descriptive statistics showed that the mean score of the experimental group increased from 76.03 in the pre-test to 84.66 in the post-test, while the control group increased from 71.38 to 76.03. The normality test indicated that the data were not normally distributed. Therefore, the Mann–Whitney U test was used to compare the post-test scores between the experimental and control groups. The result showed that the significance value (Asymp. Sig. 2-tailed) was 0.047, which is lower than 0.05. This indicates that there is a significant difference between the experimental and control groups. Based on these findings, it can be concluded that the use of flashcards is effective in improving students’ vocabulary mastery. The use of flashcards may also support a more engaging learning process.